Management of Diabetes Mellitus through Foot Exercise Activities: Literature Study - Juhanis, Juhanis; Hasmyati, Hasmyati (Institute Of Computer Science (IOCS), 2024)
According to the World Health Organization (WHO, 2020), the global prevalence of diabetes is estimated to affect around 422 million people. Foot exercise is a therapeutic practice performed by individuals diagnosed with diabetes mellitus with the aim of reducing the risk of injury and increasing blood circulation. The purpose of this study was to analyze journal findings regarding foot exercise activities in individuals diagnosed with diabetes mellitus. The method used in this study is a literature study approach. Sources of information in this article were searched through researchgate and google scholar using the keywords foot exercise and diabetes mellitus. Based on a comprehensive review of 15 scientific sources, it is known that leg exercise activities can improve blood circulation. This, in turn, results in the expansion of the capillary network, thereby increasing the availability and activity of insulin receptors. Consequently, these physiological changes contribute to reduced blood glucose levels in individuals diagnosed with diabetes.